E-046 Endovascular and microsurgical management of pericallosal aneurysms. (16th November 2010) - Hui, F; Schuette, A; Spiotta, A; Hussain, M; Moskowitz, S; Cawley, C
Abstract : Pericallosal aneurysms represent a relatively infrequent cause of subarachnoid hemorrhage (SAH). In the ISAT trial, there were 95 reported pericallosal aneurysms out of 2143 treated aneurysms, thus comprising 4.4% of aneurysms. While the ISAT broadly concluded that there was a benefit of treating ruptured anterior circulation aneurysms, studies comparing endovascular and microsurgical repair in anterior circulation aneurysms of a specific location are few. In this study, we reviewed the aneurysm databases from two institutions spanning 1999 to 2009, identifying 4456 aneurysms of which 88 were pericallosal aneurysms. Patients were classified according to presence or absence of SAH, presentation grade with Hunt and Hess scores and modified Fisher grade. Aneurysm size and method of treatment was recorded. Outcomes at latest possible follow-up date were recorded using the modified Rankin Scale (mRS). Recurrences were also noted. Statistical analysis of outcomes of aneurysm treatment were recorded comparing microsurgical and endovascular repair in both ruptured and unruptured populations. Intraprocedural rupture rates and outcome measures were compared, with craniotomy associated with greater probability of resulting in lower mRS in the acute setting (p=0.048).